STUDI DOCKING MOLEKULAR SENYAWA ASAM SINAMAT DAN DERIVATNYA SEBAGAI INHIBITOR PROTEIN 1J4X PADA SEL KANKER SERVIKS - Susmi Ferwadi; Rahmat Gunawan; Winni Astuti (JURNAL KIMIA MULAWARMAN, 2017)
Molecular docking of cinnamate acid compound and its derivatives as protein 1J4X inhibitor to cervical cancer cell has been done. The result showed that the docking energies on mode 1 of inhibitor molecules are -5.7 kcal/mol for cinnamate acid, -6.0 kcal/mol for phenyl cinnamate, -4.7 kcal/mol for methyl cinnamate and -7.5 kcal/mol for 4-phenylchroman-2-on. The inhibitor molecules were interacted with the amino acids of the cervical cancer cell by forming hydrogen bondings. Cinnamate acid formed hydrogen bondings with amino acids of serine 124, glycine 127, tyrosine 128, serine 129 and arginine 130. Phenyl cinnamate formed hydrogen bonding with amino acid of serine 129. Methyl cinnamate formed hydrogen bonding with amino acid of serine 129. 4-phenylchroman-2-on formed hydrogen bondings with amino acids of serine 124, serine 129 and arginine 130. Cinnamate acid is more potential as anticancer drug than phenyl cinnamate, methyl cinnamate and 4-phenylchroman-2-on